A CLINICAL RESEARCH-PRACTICE NEXUS AS PERCEIVED BY NURSES: NEEDS ASSESSMENT RESEARCH - Chintapanyakun, Teepatad; Wongwanich, Suwimon; Kaemkate, Wannee (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
This needs assessment research was aimed to evaluate the needs of a clinical research – practice nexus (RPN) by prioritizing the urgent needs that require to be developed, causing analysis, and determining guideline for the promotion. Four hundred and eighty-nine registered nurses and ten key informants were recruited by using purposive sampling technique from Ramathibodi hospital, Mahidol university. The instruments used for data collection were the demographic data form and the needs assessment for RPN questionnaire. The needs assessment for RPN questionnaire was tested for its content validity. Cronbach’ s alpha coefficient reliabilities were .916 - .925. Omega coefficient reliabilities were .486 - .606. The construct validity of this instrument fitted with the empirical data (c2(41, N=489) = 51.393, p = .128, CFI = .996, TLI = .994, RMSEA = .023, SRMR = .020). Data were analyzed by using descriptive statistics, the Modified Priority Needs Index (PNImodified) and content analysis. The results showed that: 1) nurses’ needs that require to be developed were capability in reading research (.43), capability in nursing practice (.39), and capability in RPN (.31) respectively, and 2) cause analysis found that nurses have been cultivated to be practitioners from the beginning. Barriers to promoting academic success among nurses were workload in taking care of a large number of patients and lack of capacity in searching and reading research articles. The guidelines for enhancing nurses to utilize the RPN in clinical practice were that having a nurse mentor, using proper technology at work, promoting reading research articles skills related to working context, and sharing advantages of utilizing the RPN in nursing practice.